Peran Lembaga Kehakiman dalam Sistem Pemerintahan Indonesia - Kheisa Rahma Adhadina; Savira Eka Kusumawati; Nanjelina Adinda Fazya; Farizki Alam; Kuswan Hadji (Perspektif Administrasi Publik dan hukum, 2024)
Indonesia is a legal state whose government system is based on applicable regulations. These regulations are carried out by several powers, namely the Executive, Legislative and Judicial powers. The purpose of this division of power is to avoid injustice due to arbitrary power. The judiciary or judicial institution is an institution whose role is to uphold justice, of course this judicial institution is very important because it is one of the basic pillars of the government system in the Republic of Indonesia. In fact, it is clearly regulated in Article 24 paragraph (1) of the 1945 Constitution which In essence, the judiciary is an institution that has independent power to administer justice to uphold justice. In this article the authors will discuss the urgency of the Judicial Institution in the government system in Indonesia and the role and operation of the judiciary in the government system. The discussion uses the Normative Juridical method, namely by studying and paying attention to Values, existing regulations.